Investigations on local structures in new Bi2−2xLa2xUO6 (x = 0–0.05) solid solutions: a combined XRD, EXAFS, PL and EPR study. Issue 18 (7th April 2016) - Sanyal, Kaushik; Pathak, Nimai; Yadav, Ashok Kumar; Kanrar, Buddhadev; Kadam, Ramakant Mahadeo; Jha, Shambhu Nath; Bhattacharya, Dibyendu; Misra, N. L.
Abstract : During the formation of Bi2−2 x La2 x UO6 ( x = 0–0.05), La +3 ions replace Bi +3 in the Bi2 UO6 lattice with the creation of some oxygen vacancies. Abstract : La doped Bi2 UO6 solid solutions of the general formula Bi2−2 x La2 x UO6 ( x = 0–0.05) were prepared by the solid state reaction of Bi2 O3, La(OH)3 and U3 O8 in a stoichiometric ratio. These solid solutions were characterized by X-ray diffraction, Extended X-ray Absorption Fine Structure (EXAFS) and X-ray Absorption Near Edge Spectroscopy (XANES) studies. It was found that La goes to the Bi sites of the Bi2 UO6 lattice during the formation of these solid solutions. For further confirmation, a photoluminescence (PL) study on an iso-structural Bi1.96 Eu0.04 UO6 was performed, and this supports the above observation. The solid solutions were also probed by EPR studies. The PL and EPR studies suggest that there are doping induced oxygen vacancies in these solid solutions.